Przekłady literatury polskiej w Korei - Choi Sung-Eun (Postscriptum Polonistyczne)
The history of translating Polish literature in South Korea goes almost 100 years back. In the article Polish literary works translated into Korean have been presented in chronological order. The first Polish literary work offered to Korean readers was Quo vadis by Henryk Sienkiewicz. It was translated from Japanese into Korean language in 1916. Since then Korean translators have been presenting Polish literature to their compatriots almost constantly and in many different ways. This also applies to the very difficult moments in the history of Korea such as Japanese occupation (1910–1940) or so called „cold war” period. Around 70 works of Polish literature have been published in Korea so far (not mentioning re‑editions and several different translations of the same work). Some works have been published several times, translated by different people and published by different publishing houses (for example Quo vadis by Henryk Sienkiewicz, Eighth day of a week by Marek Hłasko, Solaris by Stanisław Lem).